1990
DOI: 10.1007/bf00041469
|View full text |Cite
|
Sign up to set email alerts
|

Some remarks on the presence of organic phosphates in sediments

Abstract: This article describes a new method developed to assess the size and nature of the organic phosphate pool. Using sediment suspensions from the Rhone, Garonne and PO rivers, inorganic P compounds, Fe(OOH) and CaCO, were removed using mild extractants at sediment pH. The residual phosphate was then fractionated into an acid soluble organic phosphate pool and a residual organic phosphate pool by acid hydrolysis (0.5 M H + ). Both pools were quantitatively important, accounting for between 16 and 54% and 16 and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…After the removal of inorg-P by these extractions, a considerable amount of P remained fixed on the sediments . As the chelating extractants are milder than the classical extractants (NaOH and H2SO4), we believe that the remaining pool is organic -and is larger than has often been supposed (De Groot, 1990) . A considerable part of the remaining pool is extractable with H+ (Acid soluble org-P, ASOP) ; in the classical extractions this pool was extracted as CaCO3 ::~ P. After the ASOP extraction some phosphate still remains in the pellet .…”
Section: Annex I Extraction Schemementioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of inorg-P by these extractions, a considerable amount of P remained fixed on the sediments . As the chelating extractants are milder than the classical extractants (NaOH and H2SO4), we believe that the remaining pool is organic -and is larger than has often been supposed (De Groot, 1990) . A considerable part of the remaining pool is extractable with H+ (Acid soluble org-P, ASOP) ; in the classical extractions this pool was extracted as CaCO3 ::~ P. After the ASOP extraction some phosphate still remains in the pellet .…”
Section: Annex I Extraction Schemementioning
confidence: 99%
“…Since in the present extraction scheme Fe(OOH) and CaCO3 are extracted as well, this danger is no longer present . Therefore De Groot (1990) and De Groot & Golterman (1991) were able to analyse the org-P compounds further . It was found that a c o n s i d e r a b l e q u a n t i t y o f t h e o r g -P c o u l d b e e x t r a c t e d with strong acids at low concentrations (e .g .…”
Section: Organic Phosphatesmentioning
confidence: 99%
“…The extractability of this fraction may be affected by the presence of humic substances but information on this process is not available yet. Biochemical components such as nucleic acids, lipids and sugars may be included in the acid soluble Organic-P fraction [7]. Golterman et al [9] proposed another extractant for acid soluble Organic-P: 0.5M trichloroacetic acid (TCA).…”
Section: Resultsmentioning
confidence: 99%
“…Fe(OOH)-P is extracted with buffered CaEDTA/dithionite and CaCO 3 -P subsequently with Na 2 EDTA. In the next step, acid hydrolysable Organic-P (Organic-P ac ) is extracted with H 2 SO 4 [7] and then the remaining Organic-P (Organic-P alk ) Sediments receive a large amount of organic matter in eutrophic environment. Phosphorus is often responsible for this high primary production.…”
Section: Methodsmentioning
confidence: 99%
“…Acid-OP includes apatite-bound phosphate and biochemical components such as nucleic acids, lipids, and sugars that bound to phosphate (De Groot 1990). The main component of alkali-OP is humic substances (Golterman 2001).…”
Section: Discussionmentioning
confidence: 99%